A sticky situation: honeydew of the pear psylla disrupts feeding by its predator Orius sauteri. Issue 1 (8th July 2019) - Ge, Yang; Liu, Pingping; Zhang, Liu; Snyder, William E; Smith, Olivia M; Shi, Wangpeng
Abstract: Background: Honeydew is valuable food source for predators that can build predator numbers and strengthen biological control. Honeydew excreted by hemipterans often supplements the diets of their predators and parasitoids. However, dense sticky honeydew also creates a difficult foraging environment, potentially limiting predator efficiency. Results: We examined the benefits and costs of honeydew excreted by the pear psylla ( Cacopsylla chinensis [Yang and Li]) for its key predator in much of Asia, the anthocorid bug Orius sauteri (Poppius). We found these predators spent more time foraging and laid more eggs in the presence of psyllid honeydew compared to the control. However, predators more often foraged among psylla without honeydew than those coated in honeydew. This suggests that while O. sauteri recognized honeydew as a useful cue to prey presence, the predators were more likely to attack pear psylla lacking the sugary excretion. In foraging trials, honeydew consistently reduced the number of psyllids killed by the predator, suggesting it limited O. sauteri mobility or reduced the nutritional value of psyllids as prey. We also found slowed development, reduced longevity, and reduced fecundity of O. sauteri reared on moth eggs ( Sitotroga cerealella [Olivier]) coated in honeydew compared to those reared on moth eggs alone. Conclusion: Altogether, our results suggest that psyllid honeydew could serve as a prey‐location and oviposition cue for O. sauteri . However, honeydew also limited predator foraging with the potential to limit biological control. More generally, honeydew might form an important type of defense for stationary feeders like psyllids. © 2019 Society of Chemical Industry Abstract : Pear psylla ( Cacopsylla chinenesis ) honeydew attracts the predator Orius sauteri and stimulates its oviposition, but also harms O. sauteri 's larval development, foraging and longevity to the detriment of biological control.